Jet substructure templates: data-driven QCD backgrounds for fat jet searches - Cohen, Timothy; Jankowiak, Martin; Lisanti, Mariangela; Lou, Hou Keong; Wacker, Jay G. (Journal of high energy physics, 2014)
QCD is often the dominant background to new physics searches for which jet substructure provides a useful handle. Due to the challenges associated with modeling this background, data-driven approaches are necessary. This paper presents a novel method for determining QCD predictions using templates — probability distribution functions for jet substructure properties as a function of kinematic inputs. Templates can be extracted from a control region and then used to compute background distributions in the signal region. Using Monte Carlo, we illustrate the procedure with two case studies and show that the template approach effectively models the relevant QCD background. This work strongly motivates the application of these techniques to LHC data.
Gesehen am 25.08.2020